Apigenin Attenuates the Allergic Reactions by Competitively Binding to ER With Estradiol - Yao, Lu; Fan, Zhuoyan; Han, Shiwen; Sun, Na; Che, Huilian (Frontiers in Pharmacology, 2020)
Apigenin is a natural phytoestrogen with properties including anti-inflammatory and other abilities. This study aims to 1) systematically validate that excessive estrogen exacerbates allergic reactions; 2) explore the anti-allergic effects and mechanisms of apigenin. We conduct a survey of college students, indicating that of the 505 effective results, 70 individuals were self-reported allergic and 74.1% of them were women, which proved the gender difference in allergic reactions. BALB/c mice are grouped into the negative control group (Neg-Ctrl), the OVA-sensitized group (Ctrl), the estrogenized OVA-sensitized group (E2), and three treatment groups administrating different dose of apigenin. In vivo data indicated that apigenin treatment significantly inhibited the enhancement of estradiol on clinical symptoms. Moreover, we found that high doses of apigenin inhibited Th2 type humoral response and mast cell degranulation levels in vivo and in vitro. Additionally, medium and high doses of apigenin significantly reduced the potentiation of estradiol on ER expression, attenuated the transmission of estrogen/ER signaling, thereby inhibiting the phosphorylation of ERK1/2 and JNK1/2/3 in the MAPK. Besides, we found that apigenin competitively bound to ER with estradiol, and showed a weak selectivity to ERβ. Overall, we identified apigenin can be beneficial in allergic disease.